ANALISIS HAMBATAN GURU IPS DALAM PEMBELAJARAN JARAK JAUH DAMPAK PANDEMI COVID-19 DI SMP/MTS KECAMATAN GEBOG KABUPATEN KUDUS - Ferdianita, Naila Ferdianita Naila; Mulianingsih, Ferani (Universitas Negeri Semarang, 2021)
This study aims to determine the barriers of IPS teachers in distance learning (PJJ) in Gebog District, Kudus Regency. The results of the analysis show that the covid-19 pandemic makes learning in Gebog District, Kudus Regency done with distance learning (PJJ). IPS teacher barriers in distance learning (PJJ) include; (1) differences in geographical location, (2) limitations of learning infrastructure, (3) passive learners, (4) learning assessment, (5) large learning quota, (6) teacher professional ability. And efforts in overcoming distance learning barriers (PJJ) include; (1) the policy of each school, (2) assignment of work directly (3) provision of study motivation and school visit, (4) grant of study quota from the government, (5) direct collection of duties, (6) increasing the professional ability of teachers in the use of technology and communication. Penelitian ini bertujuan untuk mengetahui hambatan guru IPS dalam pembelajaran jarak jauh (PJJ) di Kecamatan Gebog Kabupaten Kudus. Hasil analisis menunjukan adanya pandemi covid-19 menjadikan pembelajaran di Kecamatan Gebog Kabupaten Kudus dilakukan dengan pembelajaran jarak jauh (PJJ). Hambatan guru IPS dalam pembelajaran jarak jauh (PJJ) meliputi; (1) perbedaan letak geografis, (2) keterbatasan sarana prasarana pembelajaran, (3) peserta didik pasif, (4) penilaian pembelajaran, (5) kuota belajar yang besar, (6) kemampuan profesional guru. Dan upaya dalam mengatasi hambatan pembelajaran jarak jauh (PJJ) meliputi; (1) kebijakan masing-masing sekolah, (2) pemberian tugas dilakukan secara langsung (3) pemberian motivasi belajar dan school visit, (4) pemberian kuota belajar dari pemerintah, (5) pengumpulan tugas secara langsung, (6) peningkatan kemampuan profesional guru dalam penggunaan teknologi dan komunikasi.